ANTIFUNGAL ACTIVITY OF GARLIC AND NEEM EXTRACTS AGAINST COBWEB MOLD DACTYLIUM AND GREEN ROT DISEASES IN Agaricus bisporus : ANTIFUNGAL ACTIVITY OF GARLIC AND NEEM EXTRACTS AGAINST COBWEB MOLD DACTYLIUM AND GREEN ROT DISEASES IN Agaricus bisporus (Iraqi Journal of Market Research and Consumer Protection, 2023)
The study was conducted to control cobweb disease caused by Cladobotryum dendroides and green mold disease caused by Trichoderma aggressivum, which infect the white fungus Agaricus bisporus crop. The laboratory results on the pathogenicity of the two pathogenic fungi showed their ability to cause infection in the white fungus and the emergence of symptoms. The addition of garlic and neem extracts, separately, at three concentrations (0.25, 0.5, and 1%) to the   media, potato dextrose agar (PDA), led to a significant decrease in the percentage of inhibition of pathogenic fungi C. dendroides and T. aggressivum. The highest inhibition rates obtained when using garlic extract at a concentration of 1% against the two pathogenic fungi amounted to 62.93 and 74.97%, respectively, while the name extract recorded the highest inhibition rate at the same concentration, reaching 43.47 and 32.37%, respectively. Also, when testing the extracts in the traditional cultivation of white fungus, it was noted that the garlic extract at a concentration of 1% was significantly superior in controlling infection, and no symptoms appeared when using it, the use of plant extracts at different concentrations did not record a significant difference in the period required for the emergence of fungal pins compared to the control treatment without a pathogen, the highest amount of white fungus production was 1000 g/bag when using garlic extract at a concentration of 0.5% in the presence of the pathogen C. dendroides, while the highest amount of production was 1355.0 g/bag when using neem extract at a concentration of 0.25% when infected with the pathogen T. aggressivum.